Joint hypermobility in young gymnasts: Implications for injury and performance - Ross Armstong (Kazimierz Wielki University, 2018)
Objectives: Hypermobility in gymnastics has both performance and injury implications. There is a paucity of studies that have reported joint hypermobility scores in young gymnasts and there is a need to consider joint hypermobility across different gender, age and performance levels. This study aimed to report the prevalence of joint hypermobility and range of motion values for the hip, shoulder, ankle and spine in male and female gymnasts. Methods: This study determined joint hypermobility via the Beighton score and range of motion for hip flexion, extension, abduction, shoulder flexion, ankle plantarflexion and lumbar extension in 25 male gymnasts (age:10.44±2.89 years, height:142.16±20.00cm, mass: 28.00±7.43kg and 25 female gymnasts (age:11.16±2.70 years,height: 141.55±22.34cm,mass: 32.33±7.99kg). Results: Joint hypermobility ranged from 56% (male gymnasts) to 68% (female gymnasts). The highest Beighton score was observed in female gymnasts (4.76±2.05), female gymnasts ≤13 years (4.93±1.87) and male national level gymnasts (5.67±1.15). No significant differences existed for Beighton scores between male and female gymnasts for gender (p=0.26) and age (p=0.095). Significant differences existed between male and female gymnasts for left hip extension (p=0.001), right hip extension (p=0.001), left hip abduction (p=0.001), right hip abduction (p=0.001) and lumbar extension (p=0.001) with all range of motion greater in females. For age and gender groups, significant differences existed between female gymnasts